Benefits of microwave heating method in production of activated carbon. (2nd June 2016) - Namazi, Azadeh B.; Allen, D. Grant; Jia, Charles Q.
Abstract: This work investigates the chemical activation of a biochar sample using microwaves with KOH and NaOH. The activation of char samples was carried out in a microwave oven operating at 2.45 GHz with a power input of 1200 W. The specific surface area (SSA), yield (%), and pore size distribution were studied for microwave activation with KOH and NaOH. In microwave‐assisted activation, the activation yields for NaOH and KOH activation were in the ranges of 40–70 % and 60–80 %, respectively. The NaOH‐activation takes 1.5 h in a furnace to fabricate an activated carbon with a SSA of 2600 m 2  · g −1 . However, in microwave activation, a 5 min activation with a power of 1200 W results in activated carbon with a SSA of 1900 m 2  g −1 . The activation yield and SSA are mainly controlled by impregnation ratio in microwave‐assisted activation because KOH and NaOH were the sources of heat for the activation reaction. In this work, the microwave activation increased the reaction rate by 15 times compared to the furnace activation. Microwaves have a "non‐thermal effect" on the kinetic parameters of chemical activation reactions. This effect was more evident in the case of NaOH microwave activation, probably because it is a more reactive compound compared to KOH.